(untitled) (American Journal of Pedagogical and Educational Research, 2024)
Background: Gastric cancer (GC) is the 4th most common cancer and the second most deadly cancer in the world. GC is caused by abnormal growth of gastric cells and tissues. Physical factors, infections, and genetic factors are the main risks of the disease. Purpose and Method: This study aims to investigate the prevalence of GC in patients referred to the Jamhuriat Hospital in Kabul during 2023. This study was a descriptive, cross-sectional study that was collected from the Office of the Jamhuriat Hospital’s Oncology Department in 2023. Results: In 2023, 117 patients were referred to the Jamhuriat Hospital. The prevalence of GC was (2.6%). The prevalence of GC was observed mostly in ages between 81-80 years (44.4%), male (79.5%), the Pashton race (47.9%), and smoking (61.5%). Chemotherapy (55.6%) was the common GC therapy. Most married patients, self-employed, illiterate, rural residents have several children and normal weight. Conclusion: GC is one of the most common cancers in the world, and especially in Asia, with the number of new cases growing annually. This requires observance of prevention protocols and public awareness of the risk factors.